Mind Mapping during Interactive Book Reading in Early Childhood Classrooms: Does It Support Young Children's Language Competence?. Issue 6 (18th August 2022) - Boerma, Inouk; van der Wilt, Femke; Bouwer, Renske; van der Schoot, Menno; van der Veen, Chiel
ABSTRACT: Research has shown that interactive book reading in early childhood classrooms contributes to children's language development. High quality interaction during book reading has been shown to be even more beneficial for children's language development, but more research is needed on which interaction practices really work, as there is great variability. The present study investigated the effects of three different interactive book reading approaches in an 8-week intervention: (1) interactive book reading (comparison condition), (2) book reading with focused attention, and (3) book reading using mind maps. A total of 551 children aged 4–6 years from 23 early childhood classrooms participated in the current randomized quasi-experimental study. Multilevel models were used to examine differences between conditions and/or gains in children's language competence. Research Findings: Results showed no significant differences between the three interactive book reading conditions, and no added effect of using mind maps during interactive book reading. However, our study does show that engaging young children in three different and relatively short interactive book reading interventions results in improved language competence. Practice or Policy: Findings confirm the importance of interactive book reading in education and indicate that teachers can alternate on traditional interactive reading, for example, by using mind maps.